Lakon Dewa Ruci sebagai Manifestasi Perjalanan Individual Manusia Bertemu dengan Tuhan - Halintar Cakra Padnobo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2023)
Lakon Dewa Ruci contains teachings on the union of people and The God. The problem raised in this research is how the values of the Lakon Dewa Ruci. These problems are examined by using the psychological theory of Jolan Jacobi: “De Psychology Van GG. Jung” 1971 which uses the theory of the individualization process. This research is qualitative with the data collection through observation, literature study, and interviews. The results of the research show that the human journey to reach perfection in order to meet the Almighty requires knowledge and the firm heart. The knowledge of the Tarekat, the Essence, and the Makrifat teaches humans to meet the Almighty.